Pengaruh Kualitas Produk, Brand Import dan Lifestyle Terhadap Keputusan Pembelian Pakaian Thrifting Royal Store Di Kota Bima - Yuwidasari; Muhajirin; Nur Khusnul Hamidah (Global Journal of Management, Accounting, and Financial Studies, e-ISSN: 3109-1539, 2025)
The purpose of this study was to determine the effect of product quality, imported brands and lifestyle on purchasing decisions for Royal Store Thrifting clothing in Bima City. This study was conducted at the Royal Store Bima located on Jl. Soekarno Hatta, East of Serasuba Field, Paruga, West Rasanae, Bima City. This study is an associative type using a Likert scale questionnaire as a research instrument. The population used in this study were all consumers who had purchased Royal Store thrifting clothing in Bima City whose number was not known for certain (Unknown Population). A sample of 96 people who had purchased Royal Store thrifting clothing in Bima City. The sampling technique was purposive sampling. The type of data used in this study was quantitative data with primary data as the research data source. Data collection techniques were observation, questionnaires and literature studies. Data analysis using validity test, reliability test, classical assumption test, multiple linear regression test, determination test, correlation test, t test and F test. The results of the study stated that product quality, imported brands and lifestyle have a significant influence on purchasing decisions of Thrifting Royal Store clothes in Bima City. These results prove that when a thrifting product has good quality, the original imported brand product and the product is in accordance with the customer's lifestyle, it will influence the customer's purchasing decision